Kempen kesedaran pengurusan kewangan untuk golongan muda - Muhammad Hafiz, Kamarudin (Universiti Malaysia Sarawak (UNIMAS), 2012)
Financial Management Awareness Campaign emphasizes on integrated information and visual delivery for young generation. Inforgraphic production through new media design and publication is a main creative strategy in order to promote awareness among target audience.